Sosialisai Dan Pelatihan Metode Pembelajaran Hypnoteaching Bagi Guru SMA/SMK Di Rokan Hulu - Bastian, Adolf; Firdaus, M.; Rizky, Ramanda (Faculty of Engineering University of Pahlawan Tuanku Tambusai, 2023)
Community service activities carried out by this service team at partner institutions, namely SMA/SMK in Rokanhulu Regency. The purpose of implementing this PKM activity is to improve the quality of learning in class, with socialization and Hypnoteaching learning training methods. The implementation method used is through 3 stages, namely 1) the preparation stage, the implementation stage, and 3) the evaluation stage. Based on the results of data processing, it was found that participants were able to integrate the hypnotic method into their learning process after carrying out this socialization and training activity. This activity had a positive impact on participants before and after it was given, with an average post test score of 82.50 which was very good. Meanwhile, 78% of participants stated that this PKM activity had a positive impact.